Does the Garra population (Teleostei: Cyprinidae: Labeoninae) from the Kol River drainage, Persian Gulf basin merit formal description? - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza (Zootaxa, 2021)
Recognizing and defining a species has been a controversial concern for a long time. To define the variation and the limitation between different species, especially closely related taxa in a complex species group, several concepts have been proposed which may lead to different taxonomic decisions. When a taxonomist studies a specific taxon, she/he should adopt a species concept and provide a species limitation to define the studied taxa. Garra population from the Kol River drainage, Persian Gulf basin has already been considered as Garra sp., based on molecular data, and to date no taxonomic decision has been made to provide a specific name for it. The Kol population presents several morphological characters that distinguish it from congeners: fully scaled breast; 7–8 ½ branched dorsal-fin rays; caudal fin with 16–17 branched rays and well-developed mental disc with free lateral and posterior margins. It is also distinguished from all other congeners in the Garra rufa group in Iran, by having two fixed, diagnostic nucleotide substitutions in the mtDNA COI barcode region. Furthermore, the Kol population demonstrates some distinct osteological characteristics in comparison to its closest species G. mondica. Based on the integrative molecular phylogenetic and species delimitation analyses, and morphological, osteological and distribution range data presented here, we think that the Kol River population merits formal description and can be considered as a distinct taxonomic unit (species).